Analysis of Product Inventory Control Using the Always Better Control (ABC) Method and Monte Carlo Simulation (Case Study: Bumdes Mart Bukit Intan Makmur Village) - Maya Sari, Putri; Nurainun, Tengku; Harpito, Harpito; Lubis, Fitriyani Surayya; Nur, Muhammad (Fakultas Teknik Universitas Tulang Bawang, 2026)
Bumdes Mart is a supermarket in Bukit Intan Prosperous Village, Kunto Darussalam Regency, Rokan Hulu Regency, Riau Province. Supermarkets face great challenges in managing product inventory, with frequent shortages or excess inventory due to monthly sales fluctuations. Therefore, there is a need to categorize products and estimate future sales. This study aims to categorize the product groups sold by Bumdes Mart into groups A, B, and C. Then, Monte Carlo simulation is used to predict future product sales quantities, and the ROP method is used to determine the reorder point. ABC analysis, Monte Carlo simulation, and the reorder point (ROP) method are used to develop an effective inventory control strategy and solve the problem of Bumdes Mart in Bukit Intan Prosperous Village. The comes about appear that Course A items incorporate 8 item sorts. Through Monte Carlo recreation, we decided that the anticipated esteem of future deals information isn't much diverse from the real information of the previous year, and the full mistake of each reenactment is less than 5%. The ROP of each item is: 48 boxes, 53 pieces, 133 packs, 456 pieces, 32 boxes, 6 sacks, 32 boxes and 6 packs. Keywords: ABC analysis, Monte Carlo Simulation, ROP, Stock, Stock Control